Assessing the Effect of Board Gender Diversity on CSR Reporting Through Moderating Role of Political Connections in Chinese Listed Firms - Shaheen, Riffat; Yang, Hailan; Bhutto, Muhammad Yaseen; Bala, Hussaini; Khan, Fahad Najeeb (Frontiers in Psychology, 2021)
This study departs from existing work on board gender diversity (BGD) and corporate social responsibility (CSR) reporting by analyzing and explaining the mechanism by which gender-diverse boards in politically embedded firms (PEFs) affect firms’ CSR reporting choices in a unique institutional setting of Chinese listed firms from 2010 to 2018. The following main results are obtained. First, having female directors and executives with political connections (PCs) on corporate boards improves the CSR reporting of firms. Firms with PCs have a greater possibility to issue CSR reports than their non-connected counterparts. Second, firms that have both gender diversity and PCs on their boards of directors are more likely to engage in CSR reporting. There is an indication that the presence of PCs on boards can strengthen the effect of female directors on firms’ CSR reporting. Third, the presence of female directors on corporate boards has a stronger relationship with CSR reporting in PEFs than in non-PEFs. The study concludes that both BGD and PCs on corporate boards positively influence the diffusion of CSR-related practices in the Chinese business environment.